Perlindungan pasar nasional terhadap predatory pricing di platform e-commerce: Tinjauan hukum kebijakan ekonomi di era ASEAN and China Free Trade Agreement (ACFTA) - Hasanah, Siti Inayatul (Maliki Interdisciplinary Journal, 2025)
The advent of digital technology and the liberalization of trade that has transpired as a consequence of the ASEAN-China Free Trade Agreement (ACFTA) has engendered both significant opportunities and substantial challenges for the national market, particularly within the domain of e-commerce. A significant challenge is the practice of predatory pricing, defined as the strategic pricing strategy of business actors that involves the implementation of artificially low prices with the intent of achieving market dominance and eliminating local competitors, particularly MSME players. The objective of this study is to analyze the efficacy of national economic policy legislation in addressing predatory pricing practices that have become prevalent on e-commerce platforms following the implementation of the ASEAN-China Free Trade Agreement (ACFTA). The methodological approach employed is a normative juridical approach, whereby national regulations, such as Law Number 5 Year 1999, government policies as administered by KPPU, and the most recent digital trade regulations, are examined. The findings indicate that despite the establishment of regulatory frameworks and law enforcement agencies, predatory pricing practices persist due to inadequate supervision and a lack of safeguards for small business actors. Consequently, there is an imperative for the reinforcement of regulatory frameworks, the promotion of synergies among institutions, and the adaptation of digital trade policies to safeguard national market sovereignty within the context of the free trade era.